Large orbital magnetic moments of small, free cobalt cluster ions Con+ with n⩽9. (30th October 2018) - Zamudio-Bayer, V; Hirsch, K; Langenberg, A; Ławicki, A; Terasaki, A; von Issendorff, B; Lau, J T
Abstract: The size dependent electronic structure and separate spin and orbital magnetic moments of free Co ( ) cluster ions have been investigated by x-ray absorption and x-ray magnetic circular dichroism spectroscopy in a cryogenic ion trap. A very large orbital magnetic moment of per atom was determined for Co, which is one order of magnitude larger than in the bulk metal. Large orbital magnetic moments per atom of ≈1 were also found for Co, Co, and Co . The orbital contribution to the total magnetic moment shows a non-monotonic cluster size dependence: The orbital contribution increases from a local minimum at n = 2 to a local maximum at n = 5 and then decreases with increasing cluster size. The 3 d spin magnetic moment per atom is nearly constant and is solely defined by the number of 3 d holes which shows that the 3 d majority spin states are fully occupied, that is, 3 d hole spin polarization is 100%.